Factors Influencing Preventive Behaviors of Nursing Students against Nosocomial Infections - Wiriyasirikul, Napawan; Thanormchayathawat, Benjawan (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
Nosocomial infection is a common type of complications and usually serious. Thus, nursing students should be careful in dealing with patients. Observing nosocomial preventive and control measures is very crucial. This research aimed to study the level of preventive behaviors against nosocomial infections and factors predicting the behaviors. Data were collected from 108 third-year and fourth-year nursing students who were enrolling in Boromarajonani College of Nursing, Nakhon Si Thammarat. They were selected by means of simple random sampling. A set of 4 questionnaires were used as research instruments to elicit general information, knowledge about nosocomial infections, awareness of nosocomial infections and preventive behaviors regarding against nosocomial infections; respectively. Results revealed that the students’ preventive behaviors against nosocomial infections in overall and in each aspect were at high levels; namely in the aspects of using preventive tools, washing hands, environment and waste management, and prevention of accidents. The factor of perceived barriers to prevention of the infections predicted the behaviors of nursing students with statistical significance indicating 14.8 percent of the variance (R2=.148, p<.01). The findings can be used to plan and develop teaching and learning procedures for practical nursing courses. This can help nursing students to have appropriate preventive behaviors against nosocomial infections. Finally, they can provide services according to the nursing standards which will result in good quality nursing services in the future.